2021
DOI: 10.1002/ecy.3284
|View full text |Cite
|
Sign up to set email alerts
|

Frequency‐dependent tree growth depends on climate

Abstract: Climate and competition interact to affect species' performance, such as growth and survival, and help determine species distributions and coexistence. However, it is unclear how climatic conditions modulate frequency-dependent performance, that is, how performance changes as a species becomes locally rare or common. This is critical because declines in performance as a species becomes more common (negative frequency dependence) is a signature of niche differences among species that stabilize coexistence, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…This finding contradicts predictions of the SGH (Bertness & Callaway, 1994) and contributes to an increasing body of evidence that in severely water‐limited environments, plant–plant interactions often become increasingly competitive, rather than facilitative (Barron‐Gafford et al., 2017; Maestre & Cortina, 2004; O'Brien et al., 2017; Tielbörger & Kadmon, 2000). Further, our finding that stronger competition was associated with reduced precipitation is supported by previous similar studies that assess how temporal variation in rainfall determines the nature of plant–plant interactions (Diez et al., 2021; Tielbörger & Kadmon, 2000) and by a recent study that found drought tended to increase competition‐induced tree mortality across parts of Europe (Kulha et al., 2023). Stronger competition in dry conditions has important implications for tree growth in future climatic conditions, in which drought frequency and severity is expected to increase (Dai, 2013; Reichstein et al., 2013).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This finding contradicts predictions of the SGH (Bertness & Callaway, 1994) and contributes to an increasing body of evidence that in severely water‐limited environments, plant–plant interactions often become increasingly competitive, rather than facilitative (Barron‐Gafford et al., 2017; Maestre & Cortina, 2004; O'Brien et al., 2017; Tielbörger & Kadmon, 2000). Further, our finding that stronger competition was associated with reduced precipitation is supported by previous similar studies that assess how temporal variation in rainfall determines the nature of plant–plant interactions (Diez et al., 2021; Tielbörger & Kadmon, 2000) and by a recent study that found drought tended to increase competition‐induced tree mortality across parts of Europe (Kulha et al., 2023). Stronger competition in dry conditions has important implications for tree growth in future climatic conditions, in which drought frequency and severity is expected to increase (Dai, 2013; Reichstein et al., 2013).…”
Section: Discussionsupporting
confidence: 87%
“…Our hypothesis regarding neighbour identity is based on the fact that species-specific neighbour effects have been shown in this system previously (Britton et al, 2022). Finally, in contrast to the SGH (Bertness & Callaway, 1994), we expect the effect of neighbours to be strongest in the driest and hottest year when competition for water will be most intense, as seen in other tests of the SGH to temporal variation in rainfall (Diez et al, 2021;Tielbörger & Kadmon, 2000, but see Sthultz et al, 2007).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…According to this theory, as densities in the natal stream increase, juvenile salmonids should increasingly select habitats with lower densities to access the resources they need for growth prior to migration. Furthermore, the effects of population density on life‐history prevalence can be mediated by environmental factors (Brown, White, & Peet, 2021 ; Diez et al, 2021 ), and the effects of environmental drivers on life‐history prevalence may increase near carrying capacity (Jesmer et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%